Processos de subjetivação no discurso religioso de matriz africana em textos de Jorge Amado - Castejon, Mariângela (2023)
This work starts from the foundation that there are educational processes in religious discourse. In this way, we consider that teaching and learning are made possible by rituals, actions, symbolization and meanings of identity, cultural and historical-social processes that permeate literary discursivity. Also, that religious discursive formations are organized and are present in literary discursivity, constituting meanings in the movements in and of history, in the composition of the subjects of the discourse and their identities. Therefore, the purpose of this study is to analyze, through subjectivation and objectification practices, the subjectivities that involve the voices that emerge in the religious discourse of African origin in the works Jubiabá, Mar morto and Tenda dos Milagres, by Jorge Amado, specifically in the terreiros de Candomblé and places of residence of the characters described in the mentioned works. To do so, we adopted discourse analysis procedures from the Foucaultian perspective, featuring a qualitative methodology, based on a proposal by Rosa Maria Bueno Fisher, through our analyses, we were able to verify that the silencing and subjectivities produced in the communities described are marks of historicity that flow and underline resistances and struggles that preserve values and demarcate ethnic, cultural statements, manifestations of faith and belonging of the subjects characters of the Amado’s literary works, starting from four different perspectives: educational processes, socialpolitical, female profiles and religiosity.